PENGARUH GOOD CORPORATE GOVERNANCE, INTENSITAS MODAL, DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI - Elizabeth Nathania Putri (2023)
This quantitative research aims to analyse the effect of good corporate governance mechanism (managerial ownership & independent commissionaire) on accounting conservatism. The population of this research are non-financial companies listed on the Indonesia Stock Exchange in 2019 - 2021 which consists of 229 companies and obtained 675 samples using purposive sampling as a method to determine the sample. Hypothesis testing using regression analysis with Stata version 13. Results of this study indicate that financial distress has a significant negative effect on accounting conservatism, meanwhile managerial ownership, independent commissionaire, and capital intensity have no significant effect on accounting conservatism.